What is new about mild temperature sensing? A review of recent findings. Issue 2 (3rd April 2019) - García-Ávila, Miriam; Islas, León D.
ABSTRACT: The superfamily of Transient Receptor Potential (TRP) channels is composed by a group of calcium-permeable ionic channels with a generally shared topology. The thermoTRP channels are a subgroup of 11 members, found in the TRPA, TRPV, TRPC, and TRPM subfamilies. Historically, members of this subgroup have been classified as cold, warm or hot-specific temperature sensors. Recently, new experimental results have shown that the role that has been given to the thermoTRPs in thermosensation is not necessarily strict. In addition, it has been shown that these channels activate over temperature ranges, which can have variations depending on the species and the interaction with a specific biological context. Investigation of these interactions could help to elucidate the mechanisms of activation by temperature, which remains uncertain. Abbreviations: Cryo-EM: Cryogenic electron microscopy; DRG: Dorsal root ganglia; H: Human; ROS: Reactive Oxygen Species; TG: Trigeminal ganglia; TRP: Transient Receptor Potential; TRPA: TRP ankyrin; TRPV: TRP vanilloid; TRPC: TRP canonical; TRPM: TRP melastatin